INFLUENCE OF NITROGEN FERTILIZERS ON THE FORMATION OF CORN GRAIN YIELD AND NITROGENUSE EFFICIENCY - Ivaniuk, В.; Hnativ, П.; Olifir, Ю. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The yield potential of modern maize hybrids has increased significantly. It is important to analyze the probable optimal rates of corn fertilization in the Small Polissya zone on sod-carbonate soils to realize the biotic potential of the crop. The aim of our study was to determine the agronomic and economic feasibility of increasing the nitrogen fertilizer rate of Pioneer P9071 (Maxim XL) hybrid corn for maximum yield. The research methods – field and laboratory. Geographical coordinates of the research site location: 49 ° 95′31 N 24 ° 84′83 ″ E. Five repetitions of the variants were used. Placement of the variants is randomized. The total area of the plot is 35 m2, accounting area – 15 m2. Corn cultivation techniques – traditional with the use of shelf cultivation. The planting rates of the hybrid was 78 000 seeds per hectare. Predecessor – winter wheat. Mathematical and statistical processing of the obtained research results and yield data was carried out using Microsoft Excel and Statistica 12.0. Data in the tables and graphs are presented as arithmetic mean with the standard deviation (x ± SD). Increasing the application of nitrogen fertilizers for corn from N90 to N125-150 improved biometric properties of the crop in such indicators as the weight of grain in the cob and the weight of 1000 grains. Maize grain yield was formed maximum when the N150 norm was applied, but it did not differ significantly from the N125 norm and amounted to 12.99–13.28 t/ha, which was 20.8–23.5 % more than in the control without nitrogen application. The yield of each additional kilogram of nitrogen in corn grain gradually reduced. Maximum nitrogen levels did not improve the content of fats and proteins in grain, but due to the increase in its collection led to a significant increase in nutrient yield to the highest level – 0.44 t/ha of fats and 1.26–1.29 t/ha of protein. According to the results of studying the effect of nitrogen fertilizer rates on the productivity of corn, the authors of the research recommend applying N125 with the division of the rate into two doses: N90 for pre-sowing cultivation and N35 – in the phase ВВСН 16–17. This ensured the production of 12.99 t/ha of high quality grain at lower nitrogen fertilizer costs.